Effect of alumina particle size on properties of electrolessly deposited composite Ni-P/Al2O3 - Chien, Ha Manh; Tung, Mai Thanh; Anh Dung, Dang Viet; Hung, Hoang Van (Vietnam Journal of Chemistry, 2014)
In this study, effect of particle size on morphology, alumina content and hardness of electrolessly deposited composite Ni-P/Al2O3 layers was examined with diffrent sizes of codeposited alumina particles. Results on Scanning Electron Microscopy (SEM), Energy Dispersed Spectroscopy (EDS), X-ray Diffraction (XRD) and hardness measurements showed that as particles size increased composition of NiP matrix did not change remarkbly e.g the composition of the obtaiend matrix ranged from Ni90P10 to Ni91P9. Meanwhile, Al2O3 content in the composites increased as particle size decreased. As a result, hardness of the obtained layers increased with decreasing particle size and maximum hardness was achieved with particle size of 0.6mm.